Removing prior particle boundaries in a powder superalloy based on the interaction between pulsed electric current and chain-like structure. (10th October 2021) - Qin, Shuyang; Yan, Longge; Zhang, Xinfang
Abstract: The chain-like prior particle boundaries (PPBs) as a kind of stubborn harmful precipitate will hinder atomic diffusion and particle connection. They can only be broken into nanoscale through thermal deformation (1160–1200 °C). Here, treated by the pulsed electric current at 800 °C, PPBs were dissolved quickly as a result of the interaction between the pulsed electric current and the chain-like structure. According to the electromigration theory and the calculation results, the high current density regions will be mainly produced at the gaps due to the conductivity difference between the precipitates and the matrix. The atomic diffusion flux caused by the pulsed electric current is proportional to the current density. Therefore, the existence of a large number of gaps in the chain-like PPBs will make the high current density regions play a more positive role in fast-dissolution.